Tedak Siten Dalam Perspektif Hukum Modern - Dyastuti, Risqi Mumpuni; Sinaga, Roulinta Yesvery (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
Tedak Siten’s culture challenges and changes that need attention. The influence of modernization and shifting cultural values has brought changes in the implementation of this tradition. Some families prefer events that are simpler and more practical, by reducing the complex traditional elements. The purpose of the Research: This research aims to identify tedak siten culture modern law perspective. Research method: This research is doctrinal research using secondary data. The secondary data used is primary legal material, secondary legal material, and tertiary legal material. Library research is used as technique of data collection. Furthermore, technique of analysis data used in this research is qualitative data analysis with historical approach. Research Finding: Cultural and legal relations are dynamic, interactive and dialectical, in this relationship allows law as a shaper as well as an object of cultural study, and / or change positions circularly, which is turn and formed the other. In Legal Theory it is known that the learning contains legal structure, legal substance and legal culture. The current modern situation in the implementation of cultural preservation still refers to culture and law, it's just that material simplification is carried out in the implementation of ceremonies and equipment to make it more practical.